From 1D convolutional codes to 2D convolutional codes of rate 1/n - Almeida, Paulo J. (2015)
In this paper we introduce a new type of superregular matrices that give rise to novel constructions of two-dimensional (2D) convolutional codes with finite support. These codes are of rate 1=n and degree d with n d +1 and achieve the maximum possible distance among all 2D convolutional codes with finite support with the same parameters.